Le bien de l’homme chez Spinoza : vers un existentialisme positif - Ursula Renz (Astérion)
How can the conception of man in Spinoza’s metaphysical principles and concepts put forward in parts one and two of the Ethics be reconciled with the orientation towards the human good in Spinoza’s views on ethics and politics? This article sets out to dispel this tension by ascribing a kind of existentialism to Spinoza. This existentialism is characterised neither by an emphasis on human mortality, nor by the invocation of the idea of human possibility. Instead, Spinozistic existentialism uses a wholly positive notion of the finitude of human existence, and it is from this idea that the notion of humanity is derived. While this existentialist interpretation of Spinozism requires us to refrain from interpreting Spinoza’s famous conatus doctrine in essentialist terms, it does not deny that this notion is used by Spinoza to defend his incremental naturalism. It rather indicates that, in contrast to the existentialist approaches of Jean-Paul Sartre and Martin Heidegger, Spinoza’s version of existentialism is not opposed to naturalism. The article concludes with the dual hypothesis that inherent in Spinoza’s rationalism is the notion of man’s having access to the fundamental properties of being, namely the intelligibility and perfection of all beings, and that that can be experienced in shared human emotional experiences.